2021
DOI: 10.1016/j.cell.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A global metagenomic map of urban microbiomes and antimicrobial resistance

Abstract: Highlights d Cities possess a consistent ''core'' set of non-human microbes d Urban microbiomes echo important features of cities and city-life d Antimicrobial resistance genes are widespread in cities d Cities contain many novel bacterial and viral species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
190
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(217 citation statements)
references
References 88 publications
(125 reference statements)
11
190
1
Order By: Relevance
“…The variation in microbiome structure and composition may provide forensic evidence based on host lifestyle and pharmaceutical use (Gonzalez et al, 2016;Kuntz and Gilbert, 2017). A recent study highlighted the potential forensic applications based on geographic classification utilizing city-specific microbiomes (Danko et al, 2021). However, in reality, the available microbial databases are inadequate under various conditions (Hampton-Marcell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in microbiome structure and composition may provide forensic evidence based on host lifestyle and pharmaceutical use (Gonzalez et al, 2016;Kuntz and Gilbert, 2017). A recent study highlighted the potential forensic applications based on geographic classification utilizing city-specific microbiomes (Danko et al, 2021). However, in reality, the available microbial databases are inadequate under various conditions (Hampton-Marcell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the diverse location across different climate zones can also be accurately explained by the microbiome and can be used to predict the suspect's identity (Chase et al, 2016). A recent study even identified the urban microbiomes and antimicrobial resistance genes, which reflect the significant features of cities, and highlighted their forensic applications (Danko et al, 2021).…”
Section: Forensic Applications Of Microbiomementioning
confidence: 99%
“…Microorganisms associated with fabrics have not historically been studied in detail ( Buschle-Diller et al, 1994 ; Cappitelli and Sorlini, 2008 ; Linacre et al, 2010 ; Daly et al, 2012 ; Lee et al, 2016 ), whereas microbiome of human ( Turnbaugh et al, 2007 ; Nelson et al, 2010 ; Jensen, 2013 ; Shafquat et al, 2014 ) and built environments ( Danko et al, 2021a ), including closed habitat of ISS environment ( Singh et al, 2018 ; Checinska Sielaff et al, 2019 ), has received much attention ( Westwood et al, 2014 ; Kettleson et al, 2015 ; Chase et al, 2016 ; Lax et al, 2017 ). One of the objectives of this study was determining if a human within a spacesuit could act as a source for the unintentional microbial contamination and pass on microbial signatures out of the spacesuits.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2006, the field of genomics has been revolutionized by the development of next-generation sequencing technologies, enabling the comprehensive understanding of the microbial ecology of built environments such as offices ( Chase et al, 2016 ), hospitals ( Westwood et al, 2014 ), and transportation system environments ( Hsu et al, 2016 ; Danko et al, 2021a ) where humans spend a significant fraction of their time. Subsequently, molecular microbial community analyses were implemented to monitor the International Space Station (ISS) ( Singh et al, 2018 ; Checinska Sielaff et al, 2019 ) and spacecraft assembly cleanrooms ( Danko et al, 2021b ) but this is the first report measuring spacesuit microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…A recent metagenomic study of mass transit systems across 60 cities around the world has also found a low abundance of antibiotic resistance genes ( Danko et al, 2021 ). The authors used metagenomics to identify that 2,210 out of 4,728 samples had AMR gene sequences, of which the most common antibiotic resistance detected was for macrolides, lincosamides, streptogamines (MLS), and beta lactams; some of the most commonly used antibiotics to treat bacterial infection in humans.…”
Section: Antimicrobial Resistance Of Staphylococcus Aureusmentioning
confidence: 99%